INTEGRASI SAINS DAN AL-QUR’AN PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD WAHDAH ISLAMIC SCHOOL 03 MAKASSAR - Aqlia, Nur; Ismail; Ali, Khumaidi (JURNAL KAJIAN ISLAM MODERN, 2025)
The integrative learning approach at SD Wahdah Islamic School 03 Makassar combines several disciplines, such as Islamic Religious Education (PAI) and science, to provide students with a holistic understanding relevant to everyday life. This research is qualitative in nature, utilizing a case study approach. Data collection techniques include observation, interviews, and documentation. The data analysis technique involves data condensation, data presentation, and conclusion drawing, while data validity is checked through source and method triangulation. The research findings indicate that (1) The planning of integrative learning between science and the Qur'an at SD Wahdah Islamic School 03 Makassar begins with work meetings and the preparation of teaching materials. This planning is grounded in theoretical, philosophical, legal, and Islamic educational foundations, providing a strong basis for its implementation. (2) The integrative learning of science and the Qur'an at SD Wahdah Islamic School 03 Makassar is conducted with a balanced time allocation between religious and scientific subjects. (3) The evaluation of integrative learning between science and the Qur'an is carried out.